Effect of general anesthesia on pulmonary function and clinical status on children with cystic fibrosis. Issue 2 (4th September 2013) - Pandit, Chetan; Valentin, Roumel; De, Jonathan; Robinson, Paul; Fitzgerald, Dominic; van, Peter; Baines, David; Cooper, Peter; Selvadurai, Hiran; Davidson, Andrew
Summary Introduction Children with cystic fibrosis (CF) receive general anesthesia (GA) for a variety of different procedures. Historical studies assessing risk of GA report a high risk of morbidity. There is a paucity of data evaluating the risk of currently available anesthetic agents. The aim of this study was to assess the effect of GA on clinical status and lung function on children with CF. Methods Children with CF aged 8–18 years admitted for IV antibiotic treatment for a pulmonary exacerbation were invited to participate. Spirometry, forced oscillation technique (FOT), and CF clinical score (CFCS) were measured pre‐GA, at 24 and 48 h post‐GA. The nature and duration of the GA were recorded. Results Twenty two patients were recruited of which 19 patients (mean age 11.4 years, range 8–18 years, 12 male) required GA. Typically, either propofol or sevoflurane was used as induction agent and maintenance of anesthesia was with sevoflurane. A laryngeal mask was used in most cases. FEV1 mean (±SD) pre‐GA was 75.1% (±23.46) which decreased at 24 h to 74.8 (±23.0) and at 48 h to 74.3 (±20.5). FOT resistance and reactance decreased at 24 and 48 h from baseline. Changes in spirometry and CFCS were not statistically significant. Two adverse events were observed in this cohort. Conclusion The results suggest that children with mild to moderate CF lung disease do not experience significant deterioration in central or peripheral airway function following GA. The low rate of complications suggests an improved level of safety for children with CF with modern anesthesia compared with historical published data.